Իրավունքի գերակայությունը որպես պետական իշխանության կատարելագործման երաշխիք - Արմեն Ասատրյան (ՀՀ ԳԱԱ հրատ.)
Соотношение верховенства права с концепцией правового государства является актуальной проблемой. В статье представлены роль и значение верховенства права в деле совершенствования государственной власти. Проведенный анализ позволяет заключить,что верховенство права более общее, действующее во всех общественных системах положение,чем правовое государство и характерные ему принципы.Верховенство права является не принципом правового государства, а всеобщим принципом права,которое действует в правовой системе общества благодаря свойствам, характерным праву, оказывая системообразующее влияние на все общественные подсистемы, в том числе на государство как главный субьект политической системы.The interrelation of the rule of law with the concept of the legal state is an actual problem. The article presents the role and importance of the rule of law in the improvement of public authorities. The analysis allows us to conclude that the rule of law is a more generally acting state in all social systems than the legal state and the principles of its characteristics. The rule of law is not the principle of legal state but a universal principle of law, which operates in the legal system of the society due to the properties characteristic of law, leaving the system–effects on all social subsystems, including the state as the main subject’s political system.
Keywords: Law